Fabrication and properties of yttria, ceria doped zirconia-aluminia ceramic composites - Lyubushkin, R.A.; Ivanov, O.N.; Chuev, V.P.; Buzov, A.A. (Вопросы атомной науки и техники, 2011)
At present, zirconia-based ceramics are gaining popularity in dentistry, particularly in fixed prosthodontics. clinically, it is important that ceramic restorations reproduce the translucency and color of natural teeth. Zirconia based ceramics is a high performance material with excellent biocompatibility and mechanical properties, which suggest its suitability for posterior fixed partial dentures. Y₂O₃-stabilized tetragonal zirconia polycrystalline (YTZ/Al₂O₃) and CeO₂-stabilized tetragonal zirconia polycrystalline (CZA) ceramics with high-performance were prepared for dental application by use the wet chemical route, consolidated by cold isostatic pressing, and two-step sintering method. Physical and mechanical properties test results show that the bending strength, fracture toughness, and the density of full sintered ceramics suggest that the material is relatively suitable for dental restoration. В даний час кераміка на основі діоксиду цирконію набуває великої популярності в стоматологічному протезуванні зважаючи на виняткові механічні та косметичні (прозорість і колір природних зубів) властивості, біоінертність. Композиційна кераміка Y₀.₁Zr₀.₉O₂/Al₂O₃-CeO₂ була синтезована зворотним співосадженням з водних розчинів і компактуванням методом холодного ізостатичного пресування та поетапного спікання на повітрі. Охарактеризовано властивості вихідного порошку методами БЕТ, просвічуючої мікроскопії і диференціальної скануючої калориметрії. Вивчено мікроструктуру, фазовий склад, мікротвердість і міцність на стискання консолідованого Y₀.₁Zr₀.₉O₂/Al₂O₃-CeO₂. В настоящее время керамика на основе диоксида циркония приобретает большую популярность в стоматологическом протезировании ввиду исключительных механических и косметических (прозрачность и цвет естественных зубов) свойств, биоинертности. Композиционная керамика Y₀.₁Zr₀.₉O₂/Al₂O₃-CeO₂ была синтезирована обратным соосаждением из водных растворов, компактирована методом холодного изостатического прессования и спечена пошагово на воздухе. Охарактеризованы свойства исходного порошка методами БЭТ, просвечивающей микроскопии и дифференциальной сканирующей калориметрии. Изучена микроструктура, фазовый состав, микротвердость и прочность на сжатие консолидированного Y₀.₁Zr₀.₉O₂/Al₂O₃-CeO₂.